Penyuluhan serta Pendampingan Gizi dan Kesehatan di Desa Telemow Kecamatan Sepaku Kabupaten Penajam Paser Utara Kalimantan Timur - Riski Sulistiarini; Novita Eka Kartab Putri; Ika Wirya Wirawanti; Nur Rezky Khairun Nisaa; Ummi Khuzaimah; Fathul Jannah; Nur Shidiq; Kasdi Kasdi; Yuni Fardalianna; Gayuk Kalih Prasesti (Universitas Pahlawan Tuanku Tambusai, 2023)
Socioeconomic status and family food habits are one of the factors for stunting. The purpose of this community service activity is a form of stunting prevention in the community by conducting socialization and workshop activities. In the framework of nutritional and health assistance with the theme isi piringku, it is hoped that the incidence of stunting can be reduced. With this activity, it is also hoped that people can sort and choose healthy and nutritious food that can be obtained easily, cheaply and affordably. The targets of this activity include PKK cadres, posyandu cadres and mothers with toddlers who are stunted in Telemow Village, Sepaku District, North Penajam Paser Regency. Socialization activities and workshops ran smoothly and without any problems. All residents followed the training process carefully and with great enthusiasm, as evidenced by the full attention of the residents until the end of the activity. Through representatives of community leaders, this activity is considered very useful as a golden opportunity to learn and in the future it is hoped that it can reduce the number of stunting that occurs in Telemow Village.